FPGA-based Digital Filter Design for Biomedical Signal - Ozpolat, Erman; Karakaya, Baris; Kaya, Turgay; Gulten, Arif (Ieee, 2016)
Over the last years, much effort has been made toward developing computerized methods to detect seizures in patients by scientists. This paper is to present a Field Programmable Gate Array (FPGA)based Fir Filter Design for Biomedical signal processing. The Electroencephalography (EEG) has been the most dependable tool used for biomedical signal processing. The digital filter is used to filter discrete time signals with the ability to modify the frequency response of the filter at any time and it is used many application such as data compression, biomedical signal processing, communication receivers, etc. The Finite Impulse Response (FIR) filter has many advantages on signal processing such that it has a simple structure, stationary response and adaptivity with embedded microprocessors. FIR filter is proposed due to facilitate structural characteristic and design properties on filtering EEG signal. The system has a computer where the design can be programmed and simulated on Xilinx FPGA ISE editor. The focus of this study is to compute FIR filter coefficients on MATLAB Filter Design Toolbox and then transfer them to embedded design on FPGA to filter EEG signal.
12th International Conference on Perspective Technologies and Methods in MEMS Design (MEMSTECH) -- APR 20-24, 2016 -- Lviv, UKRAINE
Keywords: EEG; FPGA; FIR Filter